Influence of thermal processing on chemical composition and antinutritional factors of durian (Durio zibethinus) SEED / Marina Zulkifli … [et al.] - Zulkifli, Marina; Abdullah, Noriham; Ahmad, Noorlaila; Muhammad Nurul Azmi, Aida Firdaus (Research Management Institute (RMI), 2016)
The effects of some heat treatments on the chemical composition of durian (Durio zibethinus) seeds were determined. Heat treatments applied were boiling, microwave cooking and autoclaving. The raw D.zibethinus seeds contained the highest chemical composition in terms of protein, fat, total ash, minerals, and crude fibre content. Nevertheless, boiling, microwave cooking and autoclaving processes caused significant (p < 0.05) decreases in crude protein, crude fat, total ash, mineral compositions, and crude fibre content of D.zibethinus seeds. However, all heat treatments employed significantly (p < 0.05) increased the moisture content and total carbohydrate content of D.zibethinus seeds. Heat treatments brought a total removal of ferum of treated D.zibethinus seeds. Raw and treated D.zibethinus seeds were evaluated for their antinutritional components including phytates, oxalates, saponins and tannins. Based on the results, raw D.zibethinus seeds showed the highest amount of phytates (864.94±12.24 mg/100g), oxalates (217.98±5.00 mg/100g), saponins (161.63±2.48 mg/100g) and tannins (564.44±7.18 mg/100g) while the least amount of antinutritional components were recorded in boiled D.zibethinus seeds with 181.32±4.46 mg/100g (79.04% reduction), 105.55±13.07 mg/100g (51.58% reduction), 60.22±1.27 mg/100g (62.74% reduction) and 232.19±4.92 mg/100g (58.79% reduction) for each phytates, oxalates, saponins and tannins respectively. All treatments conducted on D.zibethinus seeds caused significantly (p < 0.05) decreases in the level of all antinutritional factors studied as compared to the raw seeds. Boiling caused the highest reduction in the level of antinutritional factors in D.zibethinus seeds followed by autoclaving and microwave cooking.